PELAKSANAAN PEMBEBANAN NAFKAH IDDAH DAN NAFKAH MUT’AH OLEH SUAMI TERHADAP ISTRI DALAM CERAI TALAK KARENA NUSYUZ DI PENGADILAN AGAMA KELAS I-A PEKANBARU - Reisa Safira Herman; Maryati Bachtiar; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Divorce is a legal act that will certainly bring certain legal consequences.Divorce that occurs because of the divorce by the husband towards the wife, thenthe husband has the obligation to give mut'ah livelihood and iddah income to hiswife. But in divorce divorce cases, the wife does not get a living if she is nuyuz. Inpractice, the divorce divorce case in the Pekanbaru Religious Court has a wifewho obtained the living of mut'ah in a divorce divorce and also a wife who isnusyuz who earns a living in divorce divorce. The purpose of this thesis, namely:first to find out the implementation of imposition of iddah income and the living ofmut'ah by the husband on the wife in divorce divorce because Nusyuz inPekanbaru Class I-A Religious Court. Second To find out the factors that causethe burden of iddah and mut’ah by husband against wife in divorce divorcebecause of nusyuz at Pekanbaru Class I-A Religious Court.This type of research can be classified as sociological, because in this studythe author directly conducts research on the location or place under study inorder to provide a complete and clear picture of the problem under study. Thisresearch was conducted in Pekanbaru Class I-A Religious Court, while thepopulation and samples were all parties related to the problems examined in thisstudy.The results of the study two things can be concluded. The implementation ofthe imposition of iddah and the livelihood of mut'ah by the husband on the wife indivorce divorce because Nusyuz in the Pekanbaru Religious Court Class I-A hasbeen effective, but the judge should use ex officio rights to protect the rights of thewife divorced by her husband. The factors that led to the implementation of theburden of iddah and the living of mut'ah by the husband on the wife in divorcedivorce because Nusyuz in the Pekanbaru Class IA Religious Court was first,economic factors of the husband's influence in the implementation of payment ofmut'ah obligations and wage income to the wife . Secondly, a wife who submits aback suit or reconciliation to obtain mut'ah's income and iddah income.Keywords: Talak- Iddah Livelihood and Mut’ah Livelihood- Nusyuz